A niobium oxide with a shear structure and planar defects for high-power lithium ion batteries. Issue 1 (6th December 2021) - Li, Tongtong; Nam, Gyutae; Liu, Kuanting; Wang, Jeng-Han; Zhao, Bote; Ding, Yong; Soule, Luke; Avdeev, Maxim; Luo, Zheyu; Zhang, Weilin; Yuan, Tao; Jing, Panpan; et al.
Abstract : The micrometer-sized H-Nb2 O5 could achieve fast lithium-ion storage by engineering its planar defects. Abstract : The development of anode materials with high-rate capability is critical to high-power lithium batteries. T-Nb2 O5 has been widely reported to exhibit pseudocapacitive behavior and fast lithium storage capability. However, the other polymorphs of Nb2 O5 prepared at higher temperatures have the potential to achieve even higher specific capacity and tap density than T-Nb2 O5, offering higher volumetric power and energy density. Here, micrometer-sized H-Nb2 O5 with rich Wadsley planar defects (denoted as d-H-Nb2 O5 ) is designed for fast lithium storage. The performance of H-Nb2 O5 with local rearrangements of [NbO6 ] octahedra blocks surpasses that of T-Nb2 O5 in terms of specific capacity, rate capability, and stability. A wide range variation in the valence of niobium ions upon lithiation was observed for defective H-Nb2 O5 via operando X-ray absorption spectroscopy. Operando extended X-ray absorption fine structure and ex situ Raman spectroscopy analyses reveal a large and reversible distortion of the structure in the two-phase region. Computation and ex situ X-ray diffraction analysis reveal that the shear structure expands along major lithium diffusion pathways and contracts in the direction perpendicular to the shear plane. Planar defects relieve strain through perpendicular arrangements of blocks, minimizing volume change and enhancing structural stability. In addition, strong Li adsorption on planar defects enlarges intercalation capacity. Different from nanostructure engineering, our strategy to modify the planar defects in the bulk phase can effectively improve the intrinsic properties. The findings in this work offer new insights into the design of fast Li-ion storage materials in micrometer sizes through defect engineering, and the strategy is applicable to the material discovery for other energy-related applications.